Database management concepts - Adamski, Joseph J. (Course Technology, 2012)
This concise yet comprehensive introduction to fundamental database concepts is an indispensable resource to develop your knowledge of database management concepts. This book's advanced topics include distributed databases, data warehouses, stored procedures, and triggers fostering an in-depth understanding of database management that will prepare users for success in their fields.